(3GdedNU ddeJMaXjfs - (3CHh GdMSf Ydj Hf eMeO Hf Nda GdeYGaQi GdeYQha HGHf GdbGHSis; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s ((3ESeGYjd Hf Nda Hf SYjO Hf YeQGf GdCfOdSi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG WjHkG eHGQckG ajg ef MOjK CHj YHO Gddg eGdc Hf CfS QVi Gddg Yfg hENJdaJ eSFdJge dENJdGa eQGOGJge hdcfge EJabhG ai GdQZHI s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3GdESJFPGf KdGK aEf CPfhG dc aCONd hEdG aGQLY (B) (3Je GdLRA GdKGdK s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
Keywords: (3GdMOjK h GdeUWdMs